2018
DOI: 10.1093/ntr/nty061
|View full text |Cite
|
Sign up to set email alerts
|

An Ecological Momentary Assessment of Cigarette and Cigar Dual Use Among African American Young Adults

Abstract: IntroductionThe dual use of cigarettes and cigars among African American young adults is a significant public health issue. Patterns of and reasons for dual use are difficult to capture using traditional self-report methods. This study used ecological momentary assessment (EMA) to characterize patterns of dual smoking and examine the personal and environmental predictors of cigarette and cigar smoking among African American young adult dual users (ages 18–29) in real-time.MethodsFor 14 days, 64 participants sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…In relation to the former, substance use events were assessed using a dynamic-interval "coverage" survey strategy as this strategy is designed to ensure that all behavioral events of interest are documented with fidelity, as well as ensure that reports for all behaviors are balanced over the course of every day for every participant. [103][104][105][106] Specifically, participants were asked to report their usual sleep schedule, which anchored the timing of each assessment (i.e., the first assessment was four hours after waking and then three times more every four hours thereafter). At the end of each window, participants were asked, "Since last assessment, how many of each have you used: cigarettes, little cigars or cigarillos, puffs of an e-cigarette or vape pen, puffs of a hookah, puffs of marijuana (vaporized or smoked), a mix of tobacco and marijuana, and servings of alcohol."…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to the former, substance use events were assessed using a dynamic-interval "coverage" survey strategy as this strategy is designed to ensure that all behavioral events of interest are documented with fidelity, as well as ensure that reports for all behaviors are balanced over the course of every day for every participant. [103][104][105][106] Specifically, participants were asked to report their usual sleep schedule, which anchored the timing of each assessment (i.e., the first assessment was four hours after waking and then three times more every four hours thereafter). At the end of each window, participants were asked, "Since last assessment, how many of each have you used: cigarettes, little cigars or cigarillos, puffs of an e-cigarette or vape pen, puffs of a hookah, puffs of marijuana (vaporized or smoked), a mix of tobacco and marijuana, and servings of alcohol."…”
Section: Data Collectionmentioning
confidence: 99%
“…Combined in succession, these coverage reports produce near-complete and consistent use reports over relatively extended periods, partly because they require only seconds for participants to complete. [103][104][105][106] Complementing the behavioral use reports collected at the close of each coverage window, randomly prompted momentary assessments, roughly one-to-two minutes each, were used to assess cravings, affect, and social context, within each four-hour window to assess ebbs and flows randomly during the day. 104 Cravings for tobacco were assessed on a ten-point scale.…”
Section: Data Collectionmentioning
confidence: 99%
“… 16 Mead et al used ecological momentary assessments to investigate reasons for dual use of cigarettes and cigars among African American young adults. 17 The authors found that cigars and cigarettes are smoked additively, rather than by substitution. Moreover, cigars (used exclusively or with cigarettes) are more likely to be used with others and inside others’ homes, whereas cigarettes are more likely to be smoked while alone.…”
Section: Knowledge Attitudes and Behaviorsmentioning
confidence: 99%
“…Moreover, cigars (used exclusively or with cigarettes) are more likely to be used with others and inside others’ homes, whereas cigarettes are more likely to be smoked while alone. 17 Studying youth in North Carolina (NC), Osman et al found variation in single, dual, and polytobacco use by race/ethnicity over three time points from 2011 to 2015, including variation in the types of tobacco products and combinations used. 18 White and Hispanic youth were found to have higher relative risk for dual and polytobacco use than Black youth; and although types of tobacco products used varied by year and race, in 2015 e-cigarettes were the most commonly used product among single product users from all racial groups in this NC youth sample.…”
Section: Knowledge Attitudes and Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation